The Structural Model of Cyberbullying–Victimization Experience Based on Body Image Satisfaction with the Mediating Role of Self-Esteem in Adolescents - Ghoroghi, Atefeh; Belyad, Mohammad Reza; Tahmouresi, Niloufar; Zhian Bagheri, Masoumeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to investigate the structural relationship between body image satisfaction and cyberbullying–victimization experience in adolescents, with self-esteem functioning as a mediating variable. Methods and Materials: The research employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of all second-level secondary school students in Tehran during the 2023–2024 academic year. A multistage cluster sampling method was used to select 400 participants, of which 374 completed all study components. Data were collected using three validated instruments: the Cyberbullying and Victimization Experience Questionnaire (CBVEQ), the Body Image Satisfaction Scale (SWBIS), and the Rosenberg Self-Esteem Scale (RSES). Data analysis was conducted using SPSS-26 for descriptive statistics and AMOS-24 for confirmatory factor analysis and SEM to test the hypothesized mediation model. Findings: Results showed that body image satisfaction positively and significantly predicted self-esteem (β = 0.200, CR = 4.085, p < 0.001), while self-esteem negatively predicted cyberbullying–victimization experience (β = –0.317, CR = –5.236, p < 0.001). Additionally, body image satisfaction had a significant direct negative effect on cyberbullying–victimization (β = –0.531, CR = –8.789, p < 0.001). The Sobel test confirmed the mediating role of self-esteem in the relationship between body image satisfaction and cyberbullying–victimization (z = –7.784, p < 0.001), indicating a significant indirect effect (β = –0.064). Conclusion: The findings highlight the central role of self-esteem in mediating the negative association between body image satisfaction and involvement in cyberbullying. Adolescents with higher body satisfaction tend to experience greater self-esteem, which in turn reduces their vulnerability to both cyberbullying perpetration and victimization.